Modern jurisprudence - Prof. Hari Chand (International law book services, 1994)
This book provides an invaluable foundation and comprehensive introduction to the subject. It furnishes the reader with the basic principles involved and, at the same time, enables the student to reflect upon and critically analyse the law and the legal system.